2009
DOI: 10.1130/l41.1
|View full text |Cite
|
Sign up to set email alerts
|

Subducted oceanic asthenosphere and upper mantle flow beneath the Juan de Fuca slab

Abstract: Many studies have shown that typical oceanic lithosphere is underlain by a well-developed asthenosphere characterized by slow seismic velocities from ~100 to 250 km depth. However, the fate of the oceanic asthenosphere at subduction zones is poorly understood. I show here using shear-wave splitting of S waves emanating from earthquakes in the Juan de Fuca slab that upper mantle asthenospheric anisotropy beneath the slab is consistent with the presence of two distinct subducted asthenospheric layers, one with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 56 publications
(65 reference statements)
2
28
0
Order By: Relevance
“…The Arakan slab event that occurred on Julian day 209, 2008 (Table 1), yielded no suitable waveforms for splitting and will not be discussed further. Splitting delay times are generally high, with a mean of 3.0 s, similar to that found for source-side splitting in the Cascades region (2.9 s; Russo, 2009) and the Carpathian Arc (2.77 s; Russo and Mocanu, 2009). Results in Figure 10 are plotted at surface projections of the point at 200 km depth along their downgoing path from the source event to the receiver station.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…The Arakan slab event that occurred on Julian day 209, 2008 (Table 1), yielded no suitable waveforms for splitting and will not be discussed further. Splitting delay times are generally high, with a mean of 3.0 s, similar to that found for source-side splitting in the Cascades region (2.9 s; Russo, 2009) and the Carpathian Arc (2.77 s; Russo and Mocanu, 2009). Results in Figure 10 are plotted at surface projections of the point at 200 km depth along their downgoing path from the source event to the receiver station.…”
Section: Resultssupporting
confidence: 60%
“…Results in Figure 10 are plotted at surface projections of the point at 200 km depth along their downgoing path from the source event to the receiver station. This procedure allows discernment of variable upper-mantle anisotropy in the source region (Russo, 2009;Russo and Mocanu, 2009), and is predicated on results of numerical studies of S-wave-effective Fresnel zones (Zhao et al, 2000) and the effects of slowly varying anisotropy on observed splitting (Saltzer et al, 2000). As is clear from Figure 10, shear-wave splitting in the vicinity of the Arakan slab is highly variable, and appears to depend strongly on the upper-mantle volume sampled by the downgoing S waves.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations